Genomic and Haplotype Comparison of Butanol Producing Bacteria Based on 16S rDNA - Wiratno, Ekwan Nofa; Suharjono, Suharjono; Wardani, Agustin Krisna (Journal of Tropical Life Science, 2016)
High butanol demand for transportation was support to butanol development. Exploration of butanol producing bacteria using genome comparison and biogeography give role to butanol industrialization. Objective of this research are butanol production, genome comparison and haplotype analysis of butanol producing bacteria from Ranu Pani Lake sediment using 16S rDNA sequences. Highest butanol concentrations were resulted by Paenibacillus polymyxaRP 2.2 isolate (10.34 ± 0.00 g.l-1) then Bacillusmethylotrophicus RP 3.2 and Bacillusmethylotrophicus RP 7.2 isolate (10.11 ± 0.01 g.l-1 and 9.63 ± 0.01 g.l-1). Number of bases (T, C, A, G) of group 1 are similar, but different with group 2. Least G+C content is Clostridium saccharobutylicum Ox29 (51.35%) and highest is Bacillus methylotrophicus RP 7.2. Conserve region (1044 bp) of 16S rDNA higher then variative region (367 bp). The number of 319 bp is PIS whereas single tone as much as 48 bp. There are 17 conserves sequences. All of butanol producing bacterial sequences was clustered to 8 haplotype. Based on source of bacteria, there are three group of haplotype. Group A was isolated from Asia, group B was isolated from America and group C was isolated from Europe.